Analisis Gangguan Jaringan Kabel dengan Kombinasi Metode Fault Tree Analysis dan Failure Mode and Effect Analysis (Studi kasus PT. ABC) - Donar Setyajid Carel; Yuniaristanto -; Irwan Iftadi (Performa: Media Ilmiah Teknik Industri, 2005)
Papadopoulos et.al (2004) has developed system analysis method by combining the FTA and FMEA methods. Generally, the combining method consist of FTA step and FMEA step. On this research, FTA step is used to describe the problem by finding its basic events and minimal cut set. Then FMEA step is used to determine problem elimination priorities based on their Risk Priority Number (RPN) value. Severity, occurence and detection is used to determine the RPN value.